Therapeutic Treatment of Alzheimer's Disease Using Metal Complexing Agents - Price, Katherine A.; Crouch, Peter J.; White, Anthony R. (Recent Patents on CNS Drug Discovery (Discontinued), 2007)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder characterized by deposition of extracellular amyloid plaques, formation of intracellular neurofibrillary tangles and neuronal dysfunction in the brain. A growing body of evidence indicates a central role for biometals such as copper in many critical aspects of AD. The amyloid beta (Aβ) peptide and its parental molecule, the amyloid precursor protein (APP) both modulate Cu and Zn metabolism in the brain. Therefore, aberrant changes to APP or Aβ metabolism could potentially alter biometal homoestasis in AD, leading to increased free radical production and neuronal oxidative stress. Modulation of metal bioavailability in the brain has been proposed as a potential therapeutic strategy for treatment of AD patients. The lipid permeable metal complexing agent, clioquinol (CQ), has shown promising results in animal models of AD and in small clinical trials involving AD patients. Moreover, a new generation of metal-ligand based therapeutics is currently under development. Patents now cover the generation of novel metal ligand structures designed to modulate metal binding to Aβ and quench metal-mediated free radical generation. However, the mechanism by which CQ and other metal complexing agents slows cognitive decline in AD animal models and patients is unknown. Increasing evidence suggests that ligand-mediated redistribution of metals at a cellular level in the brain may be important. Further research will be necessary to fully understand the complex pathways associated with efficacious metal-based pharmaceuticals for treatment of AD.
Keywords: Alzheimer' s disease